Fundamentals of Entrepreneurship (ENT300) Business plan: Sultan Coffee Roasters / Fariz Daniel Abdul Rashid …[et al.] - Abdul Rashid, Fariz Daniel; Zaini, Fakhry Aqasha; Ahmad Saufi, Muhammad Asyraf Hakimin; Mini Walek @ Khairil Khalid, Muhammad Syakir; Mohd Yusoff, Qamarul Anwar (2021)
Sultan Coffee Roasters is a modern café for everyone to enjoy their leisure time surrounding Mayang Mall, Kuala Terengganu, according to the following business plan proposal. The company is founded by five people: the General Manager, Marketing Manager, Administration Manager, Operations Manager, and Financial Manager, with a starting capital of RM300,000. We wish to deliver a fresh brew coffee to our customers while also giving them a nice time and a comfortable atmosphere to enjoy with their family and friends as a freshly built business. Before we started the business, we obviously did a lot of research and analysis to ensure that our services would have a favorable influence on the customers. However, we have several competitors in the area, including Kopi Mesin, Tealive, and Starbucks. To compete with them, we must improve and develop the existing service, which will help the company stand out from the competition. We want to have our own brand and stand out from the competition to provide a unique customer experience. We also give a strong Wi-Fi connection, air conditioning, and a pleasant environment. This would assist the company in attracting more customers and, as a result, increasing our revenue. Sultan Coffee Roasters aims to provide people from Kuala Terengganu with a fresh experience and a wonderful memory to share with family and friends. People will find it more convenient to visit our café rather than the other. Furthermore, we offer fresh, high-quality coffee beans from around the world. This will provide a large variety of drinks for our clients to pick from. Desserts such as cookies and waffles are also available. As entrepreneurs, we expect Sultan Coffee Roasters to grow at its own pace while maintaining a healthy competitive edge. We anticipate a large profit margin from having a myriad of clients, as well as the development of our own loyal customer base. We wish to be a company that successfully meets the requirements and desires of our customers by giving only the best service.